Electric properties of metal-organic lyotropic liquid crystals - Klimusheva, G.V.; Koval'chuk, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The electric properties of pure and dye-doped potassium caproate, which in a 1:1 water solution forms at room temperature ionic lyotropic liquid crystals (ILLC) of smectic A type [1], were investigated. It carried out the comparative analysis of electric properties of the investigated objects with other molecular liquid crystals (LC). It was established, that maximal field strength (at voltages U < 2 V) in ILLC, as in the case of usual LC, takes place near the electrodes, where the double electric layer (DEL) is formed. The charge transfer in this region can be described by model of the Schottky emission through a thin dielectric layer. Introducing 0.01 wt. % of ionic polymethine dye [2,3] in ILLC results in insignificant rise of conductivity of samples and increase of thickness of DEL. For samples with Cu and covered with polyimide ITO electrodes cyclic voltage-current characteristics were obtained at different voltage polarity. The ratio of concentration of charge carriers with different signs is estimated.